Upaya Meningkatkan Kemampuan Pemahaman Matematika Siswa Dengan Model Pembelajaran Kooperatif Tipe Think Pair Share Materi Bentuk Aljabar - Br. Tarigan, Elsa (Unika Santo Thomas Medan, 2019)
The purpose of this study was to: (1) determine the level of mathematical comprehension ability of class VII students of Pancur Batu 2 Middle School before and after using the Think-Pair-Share type cooperative learning model, (2) identify the application of Think-Pair-Share typeÂ cooperative learning models in an effort to improve students' mathematical understanding skills in algebraic form operating material. This type of research is Classroom Action Research. The subjects of this study were all students of class VII-2 of Pancur Batu 2 of Junior High School. Time for implementation of semester 1 of the Academic Year 2017/2018. Data collection techniques include test and non-test techniques. The study was conducted in two cycles. The level of mathematics comprehension ability of students in the first cycle was 56.67% while the second cycle was 76.67%. The results of this study indicate an increase in students' mathematical understanding skills from cycle I to cycle II which is equal to 20%. Increased teacher activity can be seen from the average percentage of teacher activity in the first cycle is 57.14%, increasing in the second cycle to 77.14%. Increased student activity can be seen from the average percentage of student activity in the first cycle is 61.42%, increasing in the second cycle to 85.71%. Based on the results obtained from this study, it was concluded that the cooperative learning model of the Think-Pair-Share type could improve students' mathematical comprehension skills in class VII of Pancur Batu 2 of Junior High School.